Matrix Metalloproteinase 8 Expression in a Tumour Predicts a Favourable Prognosis in Pancreatic Ductal Adenocarcinoma - Kaasinen Mirjami; Hagström Jaana; Mustonen Harri; Sorsa Timo; Sund Malin; Haglund Caj; Seppänen Hanna (Switzerland, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is a significant cause of cancer-related death globally, and, despite improvements in diagnostics and treatment, survival remains poor. Matrix metalloproteinases (MMPs) are enzymes involved in stroma remodelling in inflammation and cancer. MMP-8 plays a varied prognostic role in cancers of the gastrointestinal tract. We examined the prognostic value of MMP-8 immunoexpression in tumour tissue and the amount of MMP-8-positive polymorphonuclear cells (PMNs) in PDAC and their association with immune responses using C-reactive protein (CRP) as a marker of systemic inflammation. Tumour samples from 141 PDAC patients undergoing surgery in 2002-2011 at the Department of Surgery, Helsinki University Hospital were stained immunohistochemically, for which we evaluated MMP-8 expression in cancer cells and the amount of MMP-8-positive PMNs. We assessed survival using the Kaplan-Meier analysis while uni- and multivariable analyses relied on the Cox proportional hazards model. A negative MMP-8 stain and elevated CRP level predicted a poor prognosis (hazard ratio [HR] = 6.95; 95% confidence interval (CI) 2.69-17.93; p < 0.001) compared to a positive stain and low CRP level (<10 mg/L). The absence of PMNs together with an elevated CRP level also predicted an unfavourable outcome (HR = 3.17; 95% CI 1.60-6.30; p = 0.001). MMP-8 expression in the tumour served as an independent positive prognostic factor (HR = 0.33; 95% CI 0.16-0.68; p = 0.003). Tumour MMP-8 expression and a low CRP level may predict a favourable outcome in PDAC with similar results for MMP-8-positive PMNs and low CRP levels. Tumoural MMP-8 expression represents an independent positive prognostic factor in PDAC.